Managerial Processes - An Operations Management Perspective Towards Dynamic Capabilities - Bititci, U.; Ackermann, Fran; Ates, A.; Davies, J.; Gibb, S.; MacBryde, J.; Mackay, D.; Maguire, C.; van der Meer, R.; Shafti, F. (Taylor & Francis, 2011)
Motivated by the view that the managerial processes underpin the dynamic capabilities of the firm, this article seeks to review the current state of knowledge on managerial processes and propose a research agenda towards a better understanding of managerial processes. A systematic approach to the literature review covering business process and strategic management fields concludes that managerial processes are critical for sustaining and developing competitive advantage, but our understanding as to what they are, their contents and how they function is limited. A definition for managerial processes is proposed and the context within which managerial processes function is identified. An empirically based research agenda, comprising research questions, is outlined that would serve to enhance our understanding of the managerial processes that underpin dynamic capabilities.